Bingo de Goldbach - (:unkn) unknown (Universidade Federal de Goiás, 2018)
This dissertation is theoretical and has the main objectives of proposing, unprecedentedly, the Goldbach Bingo, alluding to the Goldbach Conjecture and inspiration in the Goldbach Game. The construction of the proposal, for application in the 7th Year of Elementary School, was divided into moments such as Souza's methodology. Finally we did the analysis and justification of the importance of the proposal and the use of games in Mathematics teaching, based on the questions of Cabral and the perspectives of Regina Grando, Tizuko Kishimoto and Cristiano Muniz. Our Goldbach Bingo proposal was designed to help teachers improve content such as even and odd numbers, prime numbers, and the Sieve of Eratosthenes and also the Goldbach Conjecture.
Bingo of Goldbach
Keywords: Bingo de Goldbach; Conjectura de Goldbach; Crivo de Eratóstenes; Bingo of Goldbach; Goldbach’s conjecture; Sieve of Eratosthenes; CIENCIAS EXATAS E DA TERRA::MATEMATICA